2014
DOI: 10.1021/cm501025r
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Li2MoO3 in Constructing Li-Rich High Energy Density Cathode Materials

Abstract: Layer-structured xLi2MnO3·(1 – x)­Li M O2 are promising cathode materials for high energy-density Li-ion batteries because they deliver high capacities due to the stabilizing effect of Li2MnO3. However, the inherent disadvantages of Li2MnO3 make these materials suffer from drawbacks such as fast energy-density decay, poor rate performance and safety hazard. In this paper, we propose to replace Li2MnO3 with Li2MoO3 for constructing novel Li-rich cathode materials and evaluate its feasibility. Comprehensive stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 44 publications
5
94
1
1
Order By: Relevance
“…They also provide valuable guidance for the research and development of new electrodes for other rechargeable battery systems, such as sodium and magnesium ion batteries. The detailed synthesis was reported in our recent publications 25 . Cathode specimens were prepared by slurrying the active material with 10 wt % carbon black and 10 wt % poly-vinylidene fluoride in N-methylpyrrolidone solvent, and then coating the mixture on Al foil.…”
Section: Resultsmentioning
confidence: 99%
“…They also provide valuable guidance for the research and development of new electrodes for other rechargeable battery systems, such as sodium and magnesium ion batteries. The detailed synthesis was reported in our recent publications 25 . Cathode specimens were prepared by slurrying the active material with 10 wt % carbon black and 10 wt % poly-vinylidene fluoride in N-methylpyrrolidone solvent, and then coating the mixture on Al foil.…”
Section: Resultsmentioning
confidence: 99%
“…Before 3.8 V, it shows that there are three phase transitions during the fi rst charge. On further oxidation to about 4.25 V plateau, which is considered as the activation process of Li 2 RuO 3 , [ 9,[11][12][13] a solid solution reaction with very small lattice change occurs. During next discharge and second charge, we can observe that two-phase change happen at certain voltage (about 3.3 V for discharge and 3.8 V for charge).…”
Section: Introductionmentioning
confidence: 99%
“…101,107 Despite the small contribution of oxygen to the expected redox reaction, its electrochemical profile severely changes after the first charge process (Figure 20a). 107 Ma et al revealed that the structure of Li 2 MoO 3 underwent a significant transformation upon cycling, even for the first cycle.…”
Section: Llcs Containing Heavy Atomsmentioning
confidence: 99%
“…101,107 Despite the small contribution of oxygen to the expected redox reaction, its electrochemical profile severely changes after the first charge process (Figure 20a). 107 Ma et al revealed that the structure of Li 2 MoO 3 underwent a significant transformation upon cycling, even for the first cycle. As shown in Figures 20a and 20b, many Mo cations migrate from the TM to Li layers during the first charge process, forming a disordered O1 structure followed by partial recovery during the first discharge process.…”
Section: Llcs Containing Heavy Atomsmentioning
confidence: 99%
See 1 more Smart Citation